Review - 'The Ragged Trousered Philanthropists', 'The Nation', 25 April 1914
1914-04-25 "Review - 'The Ragged Trousered Philanthropists', 'The Nation', 25 April 1914" [t0467.jpg], 25 April 1914, The Nation